المسؤولية المدنية عن الأعطال التقنية في الحواسيب الخاملة. - علي احمد خضير (Journal of Babylon Center for Humanities Studies, 2026)
Civil liability constitutes a legal framework that defines the obligation of individuals and entities to compensate for damages arising from acts that breach their duties. With the advancement of technology and the integration of computers into all aspects of life, new challenges have emerged concerning technical failures in idle computers, which may result in material or moral damages to others. This research begins with an examination of the general concept of civil liability, then focuses specifically on tort liability arising from technical failures, considered as a result of error or negligence in maintenance, operation, or programming. Such liability requires the presence of three fundamental elements: fault, damage, and a causal relationship linking them. The study also discusses the distinction between intentional and unintentional fault in this context, and highlights the types of damages that may arise, whether material, such as data loss and financial damages, or moral, such as harm to reputation or trust. Furthermore, the research addresses legal theories dealing with the multiplicity of causes leading to damage and seeks to determine the most appropriate criterion for linking technical failure to the harmful result, ultimately holding the responsible person or entity accountable and ensuring the right of the injured party to fair compensation.